2016
DOI: 10.1590/s0080-623420160000400003
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among children under the age of one: analysis of cases after discharge from maternity *

Abstract: Objective:To analyze infant death after discharge from maternity in the time period between 2000 and 2013. Method: A cross-sectional retrospective quantitative study in a municipality northward in the state of Paraná. Data were analyzed using the SPSS®, and were subjected to Chi-square test, logistical regression, 95% confidence interval, and a significance level of p<0.05. Results: Two hundred forty-nine children were born, discharged from maternity and subsequently died; 10.1% in the neonatal period and 89.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
0
7
0
11
Order By: Relevance
“…A study carried out in the South region of the country, with the objective of analyzing infant deaths after discharge from the maternity hospital, found that post-discharge follow--up occurred for the majority of the children, predominantly in the public health services. However, this reality did not benefit all children, which shows a gap in the assistance (17) .…”
Section: Discussionmentioning
confidence: 96%
“…A study carried out in the South region of the country, with the objective of analyzing infant deaths after discharge from the maternity hospital, found that post-discharge follow--up occurred for the majority of the children, predominantly in the public health services. However, this reality did not benefit all children, which shows a gap in the assistance (17) .…”
Section: Discussionmentioning
confidence: 96%
“…Dados semelhantes foram obtidos em pesquisa realizada na 21ª RS do Paraná, com 62% dos óbitos infantis concentrados no período pós-neonatal (23) . Para haver redução dos óbitos pós-neonatais, é fundamental usufruir dos programas lançados pelo Ministério da Saúde, como o Programa Saúde da Família e o Programa Nacional de Imunizações, bem como haver investimento governamental na área social, educação e infraestrutura, para que assim melhorem os indicadores de natalidade, morbidade e mortalidade no país (24) . Ao se analisar os óbitos evitáveis em estudos semelhantes (16,25) , identificou-se elevados números de óbitos infantis reduzíveis por adequada atenção à mulher na gestação e parto e ao recém-nascido.…”
Section: Discussionunclassified
“…No entanto, o componente neonatal da mortalidade infantil permanece elevado no Brasil (9/1.000 nascidos vivos), em comparação a países latinos e europeus como Chile (5/1.000 nascidos vivos), Cuba (2/1.000 nascidos vivos) e Espanha (3/1.000 nascidos vivos) (UNICEF, 2015), apesar da melhoria geral nos indicadores de natalidade, morbidade e mortalidade brasileiros. Estes resultaram da implantação de programas na área da saúde materno-infantil e de investimentos nas áreas social, educacional e de infraestrutura (SANTOS et al, 2016). Nas últimas três décadas, o Brasil teve sucesso em reduzir os indicadores de mortalidade infantil, com uma taxa média de 5 -5,5% ao ano nas décadas de 1980 a 1990 e de 4 -4,5% ao ano desde 2000.…”
Section: Introductionunclassified
“…Este contexto evidencia a estreita relação entre assistência à gestante e ao recém-nascido (RN) durante o pré-parto, parto e os desfechos relacionados à vitalidade no período neonatal imediato (LANSKY et al, 2002;SANTOS et al, 2016).…”
Section: Introductionunclassified
See 1 more Smart Citation